Blood flow vortices adapt their behaviour to the presence of kent accessory pathway. (4th February 2022) - Borrelli, N; Di Salvo, G; Ciriello, GD; Grimaldi, N; Barracano, R; Fusco, F; Merola, A; Correra, A; Colonna, D; Palma, M; Scognamiglio, G; Russo, MG; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Blood speckle imaging (BSI) is a new speckle-tracking-based technique for the evaluation of blood flow. Ventricular flow vortices have been studied in sinus rhythm in normal and dysfunctional hearts, however, data are lacking in patients with Kent accessory pathway (KAP) and short atrio-ventricular (AV) conduction. Purpose: We aimed to evaluate the characteristics of left ventricle blood vortices in children with KAP. Methods: Nineteen paediatric patients (age 7 ± 2.9 years) were included in the study: 13 patients with manifest KAP (KAP group) and 6 age and sex -matched controls with normal AV conduction (CTR group). A thorough echocardiographic evaluation with 2D, color doppler and BSI was performed in all the included patients. BSI was recorded in apical 3-chamber view with a 6S-D probe. Vortices characteristic were analysed during filling phase of the left ventricle. We focused on the anterior vortex generated by mitral valve, which persisted longer during the cardiac cycle and is assumed to contribute to optimizing cardiac function. A standard 12-lead ECG was also recorded for each child in KAP group to esteem KAP localization. Results: According to Arruda criteria for KAP localization, all patients in KAP group manifested the accessory pathway in the septal region. All patients in CTR group presented one major anterior vortex during filling phase, while in KAP group 10 patients out of 13 (p= 0.009) lacked of this main anterior vortex, showing instead fragmented different vortices. There were no differences in term of left ventricle function (KAPg 59.8 ± 4.02% vs CTRg 59.0 ± 2.5%, p= 0.6) and global longitudinal strain (KAPg -18.6 ± 1.0% vs CTRg -19.6 ± 3.1%, p= 0.5) between the two groups. Conclusion: In our preliminary analysis, in patients with septal KAP, blood vortices adapted their diastolic traces to the septal dyssynchrony showing a fragmented pattern. We speculate this fragmentation may contribute to impair the performance of the left ventricle.